Effectiveness of health education Breast Self Examination (BSE) on knowledge of breast cancer prevention - Legi, Julita; Molintao, Winarsi; Kairupan, Michelle; Mokalu, Shania (Institute of Computer Science (IOCS), 2024)
Breast cancer remains a health issue among women of reproductive age. There is breast self-examination (BSE) to prevent breast cancer. This study aimed to examine the effectiveness of health education using a leaflet about BSE. This study was supported by Senior high school number 2 Langowan. The study sample was 30 students from ages 14 to 16 years old in grades X and XI. The knowledge in this study was categorized as good and not. The result revealed increasing students with good knowledge from 73.3 to 90.0. Using paired t-tests this study revealed the effectiveness of health education using leaflets to improve BSE knowledge. There is a need for collaboration among stakeholders to emphasize this issue.